Australian urban Indigenous smokers' perspectives on nicotine products and tobacco harm reduction. (10th May 2017) - Yuke, Kym; Ford, Pauline; Foley, Wendy; Mutch, Allyson; Fitzgerald, Lisa; Gartner, Coral
Abstract: Introduction and Aims: Indigenous Australians experience a significant gap in life expectancy compared with non‐Indigenous Australians. Indigenous communities have high‐smoking prevalence and low engagement with cessation therapies. This qualitative research, conducted in an urban Australian Indigenous community, explored smokers' views on smoking, quitting and engagement with current nicotine replacement therapies. Opinions on acceptability of tobacco harm reduction were sought. We explored the acceptability of novel nicotine products, that is, new or unfamiliar products, including non‐therapeutic options, such as e‐cigarettes. Design and Methods: Focus groups and individual interviews with adult Indigenous daily smokers (n = 27) were used. Current and novel nicotine products were displayed and demonstrated. Discussions were audio‐recorded, transcribed and analysed thematically. Results: Participants expressed interest in trying existing and novel nicotine products. Short‐to‐medium term use of nicotine replacement therapy for quitting was generally acceptable; views on long‐term use were mixed. Interest in use of tobacco substitutes depended on their perceived effectiveness, providing a 'kick' and 'relieving stress'. Desirable qualities for tobacco substitutes were identified with gender differences and product preferences noted. The unpleasant taste of existing products is a barrier to both short‐term and long‐term use. Discussion: We found substantial interest in trying some existing and novel nicotine products, mostly for short‐term use. A number of attributes were identified that would make nicotine products potentially acceptable as a long‐term substitute. Conclusions: Some participants were interested in long‐term substitution if acceptable products were available. Improvements in current products and access to novel products are needed if tobacco harm reduction is to be acceptable. [Yuke K, Ford P, Foley W, Mutch A, Fitzgerald L, Gartner C. Australian urban Indigenous smokers' perspectives on nicotine products and tobacco harm reduction. Drug Alcohol Rev 2018;37:87–96]